ASP.NET in 60 Minutes a Day - Johnson Glenn (American : Wiley, 2003)
* Introduces Microsoft's widely-used, free Web development tool to new users and to those preparing for certification
* Includes thirty one-hour lessons that recreate a typical week-long introductory seminar
* Gets readers quickly up-to-speed on using ASP.NET and Web Matrix to develop Web pages and Web services
* The author has taught ASP.NET and other Microsoft tools for Xerox Connect and other major corporations
* Companion Web site features an online presentation by the author that follows along with each chapter and includes an audio-only option for readers with dial-up Internet connection
From the Back Cover
Get up and running with ASP.NET using this innovative virtual classroom approach!
Are you ready to learn how to write clean, reusable, scalable code for Web pages using ASP.NET? Experienced trainer Glenn Johnson takes you inside his virtual classroom to provide you with seventeen one-hour lessons that recreate a typical introductory seminar on Microsoft’s scripting technology. By the end of the class, you’ll have gained the skills needed to develop stunning visual elements on your own Web pages and Web services using ASP.NET!
Discover the key concepts of ASP.NET and gradually progress through the .NET Framework
Learn how to work with Web server controls available in Visual Studio®.NET and build custom Web controls
Add security to your Web site as well as enhance its overall performance
Create custom Web controls from scratch
Perform data manipulation, sorting, and filtering using the DataGrid control
Develop ASP.NET applications using such tools as HTTP handlers and modules
Optimize software performance with ASP.NET caching
Join the author on the companion Web site in a training session. Follow along as he walks you through the online presentation for each chapter provided in streaming video or audio only. Source code is also available for download.
Keywords: ASP.NET